2022
DOI: 10.1007/s00520-022-07077-4
|View full text |Cite
|
Sign up to set email alerts
|

Utility, barriers and facilitators to the use of connected health to support families impacted by paediatric cancer: a qualitative analysis

Abstract: Aim As healthcare systems are increasingly burdened, the efficiencies and cost savings offered by connected health (CH, i.e. two-way communicative healthcare technologies such as eHealth or mHealth) present an attractive solution for supporting families impacted by cancer. More research is required, however, to examine attitudes towards CH to better facilitate its use in practice. This study seeks to examine the utility, barriers and facilitators of CH use for families affected by paediatric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our study presents an evaluation of connected injection devices to deliver r-hGH therapy using a robust methodological approach, the results of which are transferrable to digital health solutions in other therapeutic areas, especially in terms of facilitators for and barriers to technology acceptance. For example, a recent qualitative analysis concluded that barriers and facilitators should be considered for effective implementation of connected health solutions to support children with cancer and their families [ 35 ]. Although TAM is sometimes criticized for being very simplistic [ 55 ], the aim of our study was not to identify new constructs for TAM but to identify facilitators and barriers related to the core constructs of perceived usefulness and perceived ease of use that are common to other models and theories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study presents an evaluation of connected injection devices to deliver r-hGH therapy using a robust methodological approach, the results of which are transferrable to digital health solutions in other therapeutic areas, especially in terms of facilitators for and barriers to technology acceptance. For example, a recent qualitative analysis concluded that barriers and facilitators should be considered for effective implementation of connected health solutions to support children with cancer and their families [ 35 ]. Although TAM is sometimes criticized for being very simplistic [ 55 ], the aim of our study was not to identify new constructs for TAM but to identify facilitators and barriers related to the core constructs of perceived usefulness and perceived ease of use that are common to other models and theories.…”
Section: Discussionmentioning
confidence: 99%
“…Several qualitative studies exploring HCPs' perceptions about factors and barriers related to digital health acceptance in endocrinology and other therapy areas have been published in the scientific literature [29,[31][32][33][34]. Some have explored HCPs' perceptions about mHealth tools used in children's health care [29,[31][32][33][34][35][36][37], concluding that early engagement of end users is critical to the development and effective implementation of such tools to enhance patient-centric care. Notably, a mixed methods formative research study has explored technology acceptance and the use of digital health tools for the emotional support of parents of children undergoing GH treatment, using educational content to help parents and caregivers understand their children's treatment journey [38].…”
Section: Digital Health Tools For Growth Hormone Deficiencymentioning
confidence: 99%
“…Accordingly, new models of care are required to meet these significant demands. Telehealth has the capability to help address these service demands and is widely cited in the literature as a patient-centered means of rehabilitative support that may positively affect functional outcomes [36][37][38].…”
Section: Principal Findingsmentioning
confidence: 99%